Safety and efficacy of left bundle branch pacing in comparison with conventional right ventricular pacing: A systematic review and meta-analysis. Issue 27 (9th July 2021) - Liu, Xing; Li, Wenbin; Wang, Lei; Tian, Shaohua; Zhou, Xiaolin; Wu, Mingxing
Abstract: Background: Right ventricular pacing (RVP) has been widely accepted as a traditional pacing strategy, but long-term RVP has detrimental impact on ventricular synchrony. However, left bundle branch pacing (LBBP) that evolved from His-bundle pacing could maintain ventricular synchrony and overcome its clinical deficiencies such as difficulty of lead implantation, His bundle damage, and high and unstable thresholds. This analysis aimed to appraise the clinical safety and efficacy of LBBP. Methods: The Medline, PubMed, Embase, and the Cochrane Library databases from inception to November 2020 were searched for studies comparing LBBP and RVP. Results: Seven trials with 451 patients (221 patients underwent LBBP and 230 patients underwent RVP) were included in the analysis. Pooled analyses verified that the paced QRS duration (QRSd) and left ventricular mechanical synchronization parameters of the LBBP capture were similar with the native-conduction mode ( P > .7), but LBBP showed shorter QRS duration (weighted mean difference [WMD]: −33.32; 95% confidence interval [CI], −40.44 to −26.19, P < .001), better left ventricular mechanical synchrony (standard mean differences: −1.5; 95% CI: −1.85 to −1.14, P < .001) compared with RVP. No significant differences in Pacing threshold (WMD: 0.01; 95% CI: −0.08 to 0.09, P < .001), R wave amplitude (WMD: 0.04; 95% CI: −1.12 to 1.19, P = .95) were noted between LBBP and RVP. Ventricular impedance of LBBP was higher than that of RVP originally (WMD: 19.34; 95% CI: 3.13–35.56, P = .02), and there was no difference between the 2 groups after follow-up (WMD: 11.78; 95% CI: −24.48 to 48.04, P = .52). And follow-up pacing threshold of LBBP kept stability (WMD: 0.08; 95% CI: −0.09 to 0.25, P = .36). However, no statistical difference existed in ejection fraction between the 2 groups (WMD: 1.41; 95% CI: −1.72 to 4.54, P = .38). Conclusions: The safety and efficacy of LBBP was firstly verified by meta-analysis to date. LBBP markedly preserve ventricular electrical and mechanical synchrony compared with RVP. Meanwhile, LBBP had stable and excellent pacing parameters. However, LBBP could not be significant difference in ejection fraction between RVP during short- term follow-up.